Penggunaan Media Pembelajaran Power Point dalam Meningkatkan Motivasi Belajar SKI Siswa Kelas XI IPA MAS Asy Syarif Sidang Koto Laweh - Saputri, Silvia; Darfius; Kamal, Muhiddinur (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2024)
In the teaching and learning process, teaching methods and learning media are important aspects. The choice of teaching method will influence the appropriate type of learning media. Learning media acts as a teaching aid that can influence the learning climate and conditions. Learning media, especially in the era of modern technology, has a significant role in improving the quality of learning. Technology helps achieve educational goals and makes learning more interesting. The use of learning media is expected to increase student motivation, help understanding, and present information in an interesting way. The use of learning media, such as PowerPoint, is expected to encourage student learning motivation. In learning the history of Islamic culture, learning media, especially technological ones, are considered underutilized at the MAS Asy Syarif Session of Koto Laweh. This has an impact on students' lack of interest and motivation to learn. This research uses a qualitative approach with field studies, involving teachers and students as informants. Data was collected through observation, interviews and documentation studies. The results of the research show that the use of PowerPoint learning media in learning the History of Islamic Culture at MAS Asy Syarif Sidang Koto Laweh is not optimal. Teachers rarely use media, especially technological ones. This has an impact on students' lack of interest and motivation to learn. Therefore, it is necessary to innovate and develop the use of learning media, especially interactive PowerPoint, to increase student learning motivation.